2016
DOI: 10.1007/s13193-016-0547-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological Study of Limb Salvage Surgery for Osteosarcoma: Experience in a Rural Cancer Center

Abstract: Although recent multimodality therapeutic protocols have led to improved survival in osteosarcoma (OS), the outcome still remains dismal. Ongoing international multicentric trials on OS aim to randomize patients for optimum management, based on histological response to NACT. The pathologic response to neoadjuvant chemotherapy (NACT) is the most important factor predicting prognosis. In this study of 23 cases of limb salvage surgery post neoadjuvant chemotherapy, mean age was 18.3 years, with male predominance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Zhang et al, ), which was approved by the Ethics Committee of Shanghai Tenth People’s Hospital, and written informed consent was obtained from all the patients. The patients were classified into chemo‐resistant and chemo‐sensitive groups on the basis of the Huvos scoring system (Vijayanarasimha et al, ). The clinical parameters of the osteosarcoma patients in this study are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al, ), which was approved by the Ethics Committee of Shanghai Tenth People’s Hospital, and written informed consent was obtained from all the patients. The patients were classified into chemo‐resistant and chemo‐sensitive groups on the basis of the Huvos scoring system (Vijayanarasimha et al, ). The clinical parameters of the osteosarcoma patients in this study are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…[15] Response to tumor necrosis as a prognosis factor has been demonstrated in various other studies from worldwide. [18][19][20][21] The number of cycles of NACT as a prognostic factor was not demonstrated in previous studies. In our study, only 10 patients (24%) received more than four NACT cycles.…”
Section: Discussionmentioning
confidence: 99%
“…The chemoresistant and chemosensitivity patients were classified according to the Huvos scoring system. 20 , 21 The specimens were preserved at −80°C until use. The work obtained approval from the Ethics Committee of Tianjin Union Medical Center.…”
Section: Methodsmentioning
confidence: 99%